Pengembangan Media Interaktif Berbasis Microsoft Power Point untuk Peserta Didik Kelas IV Sekolah Dasar Negeri 39 Pontianak Kota - Eriza Christiana; Hery Kresnadi; Bistari Bistari (Journal on Education, 2024)
This research aims to produce a product in the form of learning media based on Microsoft PowerPoint that has been validated. The research method used is research and development or in English Research and Development (R&D) by adapting the Borg and Gall design development model. The data sources for this research are the results of observations, interviews, expert validation, student responses, and documentation during the use of Microsoft PowerPoint-based learning media. Data collection techniques in this research are observation, interviews and questionnaires. The research results show that the process of developing learning media based on Microsoft PowerPoint has gone through 7 research steps, namely potential and problems, data collection, product design, product validation, revision, testing, and revision of the final product. The level of suitability of the learning media developed is very good from the design and material aspects with an average value of 3.33 and 3.78 and the product trial results are very good with an average value of 3.53 and 3.88.